A Comparative Analysis of Disability Indicators and the State of Medical and Social Rehabilitation of Disabled People as a Result of Malignant Neoplasms of Childhood in Tashkent (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Relevance of the problem.All over the world there is a trend of increasing morbidity and mortality from malignant neoplasms, including among children [1, 2, 3, 4] . According to the International Agency for Research on Cancer ( GLOBOCAN , 2020), more than 19 million cases of malignant neoplasms have been registered worldwide  [5], of which more than 200,000 occur in children under 18 years of age.